2005
DOI: 10.1038/sj.npp.1300789
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Rapid-Onset Type of Behavioral Sensitization to Amphetamine in Mice: Role of Drug–Environment Conditioning

Abstract: A rapid-onset type of behavioral sensitization (ROBS) has been demonstrated in rats treated with a single 'priming' injection of amphetamine (AMP). In that species, however, this phenomenon was restricted to AMP-induced stereotyped behavior (SB), not occurring for the locomotor-stimulant effect (LSE) of AMP and not reflecting environment-specific sensitization. In the present study, the ROBS was characterized in the mouse. Mice received a single 'priming' intraperitoneal injection of 5.0 mg/kg AMP which was pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 44 publications
(56 reference statements)
4
33
0
2
Order By: Relevance
“…The latter possibility is unlikely, considering the low BBB passage and the brain PK profile of the main metabolite (M2). With regard to the second possibility, it has been reported that an immediate and long-lasting dopaminergic sensitization is already elicited after a single injection of amphetamine and other psychostimulants (Vanderschuren et al, 1999;Chinen et al, 2006;Kameda et al, 2011;Marinho et al, 2015). Consistently, after repeated treatment (once a day for 14 days), the compound's ability to stimulate locomotor activity occurred earlier and it was sustained longer compared with that measured after the first dose, with a significant increase with a new drug challenge after 48-hour washout.…”
Section: Discussionmentioning
confidence: 51%
“…The latter possibility is unlikely, considering the low BBB passage and the brain PK profile of the main metabolite (M2). With regard to the second possibility, it has been reported that an immediate and long-lasting dopaminergic sensitization is already elicited after a single injection of amphetamine and other psychostimulants (Vanderschuren et al, 1999;Chinen et al, 2006;Kameda et al, 2011;Marinho et al, 2015). Consistently, after repeated treatment (once a day for 14 days), the compound's ability to stimulate locomotor activity occurred earlier and it was sustained longer compared with that measured after the first dose, with a significant increase with a new drug challenge after 48-hour washout.…”
Section: Discussionmentioning
confidence: 51%
“…Since stereotypy is related to an increased dopaminergic transmission in the striatum (Canales and Graybiel, 2000;Chinen et al, 2006;Saka et al, 2004), it could be suggested that prenatal Poly(I:C) was not able to enhance the dopamine in this cerebral region. Oppositely, the maternal immune activation by LPS promoted an upregulation of D 1 receptor within the striatum (Zager et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The stereotyped behavior was quantified for 15 s, every 5 min during 100 consecutive min. The stereotypy notes were attributed as proposed by Setler et al, 1976 andChinen et al, 2006. Scores from 0 to 4 were attributed to each animal, as follows: 0) asleep or stationary; 1) active; 2) active with predominantly stereotyped sniffing and rearing; 3) stereotyped sniffing with bursts of licking and/or gnawing and biting; 4) continual licking and/or gnawing of cage grids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, previous administration of methamphetamine markedly potentiated methylphenidate-induced motor activation. It must be pointed out that the behavioral protocol used in the present study is different to that used in studies showing a rapidonset type of behavioral sensitization of psychostimulants, where the effect of a high dose (prime) of a psychostimulant potentiates the behavioral effects of a lower dose (probe) of the same or another psychostimulant (Kuczenski and Segal, 1999a, b;Chinen et al, 2006). Furthermore, at least in rats, this sensitization seems to be restricted to stereotypies, without affecting locomotion (Kuczenski and Segal, 1999a, b).…”
Section: Figurementioning
confidence: 99%